Cultural Preservation Efforts: Case of Reyog Art Performance at Muhammadiyah Ponorogo University, Indonesia - Itsnaini Muslimati Alwi; Romelah Romelah; M. Nurul Humaidi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The local cultural arts reflect the wisdom of a region and should be preserved. The reyog dance is a cultural heritage originating from Ponorogo regency. It holds historical, artistic, and social significance that is crucial to safeguard. This paper aims to describe the preservation of Reyog Ponorogo cultural arts at Muhammadiyah Ponorogo University, outline future preservation challenges, and explore the Islamic value of the art. The research methodology used is qualitative. Data was collected through interviews and supported by literature related to Reyog Ponorogo. The study results demonstrate that the preservation of Reyog Ponorogo's local cultural arts at Muhammadiyah Ponorogo University is facilitated through the Student Activity Unit of Paguyuban Seni Reyog Mahasiswa Simo Budi Utomo and via a literary collection housed in the Reyog Corner at the university library. To preserve the Reyog Ponorogo culture, the Simo Budi Utomo Unit plans to use communication strategies, education, legal protection, community involvement, technological innovation, and explore the meaning of this art form. Reyog Ponorogo dances hold Islamic meaning. Islamic values are ingrained in the preservation of Reyog Ponorogo in Simo Budi Utomo unit, namely love for Allah, the spirit of struggle and hard work, discipline, solidarity, and cohesiveness in teamwork.